Hypocrisy, skepticism, and reputation: the mediating role of corporate social responsibility. Issue 6 (2nd September 2019) - Arli, Denni; van Esch, Patrick; Northey, Gavin; Lee, Michael S.W.; Dimitriu, Radu
Abstract : Purpose: The purpose of this paper is to examine the effect of corporate hypocrisy and consumer skepticism on perceived corporate reputation. In addition, the effect of perceived corporate social responsibility (CSR) in mediating the relationship between corporate hypocrisy and consumer skepticism toward perceived corporate reputation. Design/methodology/approach: An experimental design was employed to test the effects of corporate hypocrisy and consumer skepticism on consumers' perception of a firm's corporate reputation, as well as the role of perceived CSR as a causal mechanism. Analysis involved structural equation modeling (AMOS) to test hypotheses. A convenience sample ( n =837) was recruited from the USA and Australia to allow for any national biases or brand familiarity effects and to ensure the results were robust and generalizable. Findings: Corporate hypocrisy and consumers' skepticism significantly influences perceived CSR and corporate reputation. Furthermore, a consumer's level of perceived CSR acts as a causal mechanism, mediating the relationship between corporate hypocrisy and skepticism on perceived corporate reputation. Practical implications: The importance of being transparent and honest toward consumers. When companies are inconsistent in their CSR activities, it increases consumers' skepticism toward the brand. Nonetheless, CSR has a positive influence on the consumers' perception of corporate reputation and this, in turn, will positively influences consumers' support for the firm. Originality/value: The first empirical evidence that companies producing vices (such as beer) generate lower expectations in the minds of the consumers, meaning there is less impact on brand reputation when consumers feel the CSR does not fit with the brand image.